2016
DOI: 10.5152/clinexphealthsci.2016.0052
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Factors Affecting the Quality of Life of Elderly Nursing Home Residents

Abstract: Objective:The study was performed to determine the quality of life and factors affecting the quality of life of elderly nursing home residents. Methods: This cross-sectional study was conducted with 150 elderly individuals residing in nursing homes situated in Istanbul in the period December 2013-February 2014. Data were collected using the sociodemographic questionnaire and World Health Organization Quality of Life Scale(WHO-QOL-BREF). Descriptive statistics, Mann-Whitney U test, Kruskal-Wallis test, one way … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 4 publications
1
12
0
Order By: Relevance
“…The health status of individuals can affect adaptation difficulties for the elderly 7 . The chronic diseases seen in elderly people affect the quality of life negatively 2, 18 . Also in the current study, it was identified that elderly people who have chronic diseases, who use drugs regularly, and who have a poor health perception have more adaptation difficulty, and that they use positive religious coping.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…The health status of individuals can affect adaptation difficulties for the elderly 7 . The chronic diseases seen in elderly people affect the quality of life negatively 2, 18 . Also in the current study, it was identified that elderly people who have chronic diseases, who use drugs regularly, and who have a poor health perception have more adaptation difficulty, and that they use positive religious coping.…”
Section: Discussionmentioning
confidence: 51%
“…7 The chronic diseases seen in elderly people affect the quality of life negatively. 2,18 Also in the current study, it was identified that elderly people who have chronic diseases, who found to be better than women's adaptation to ageing. 1,7,17 Adaptation to the process of ageing was examined in four sub-dimensions including 'Role and Self-actualisation Mode', 'Interdependence Mode', 'Physiological Mode' and the 'Self-concept Mode'.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…In the studies conducted in the literature, it is reported that the quality of life of elderly individuals are negatively affected by the factors such as chronic illness (İlhan, Arpacı, Havaoğlu, Kalyoncuoğlu, Sarı, 2016), multiple drug use (Gencer & Arica, 2017), long-term inpatient treatment (Yılmaz & Tekin, 2017), urinary incontinence (Demir & Erbesler, 2017), and living alone (Gencer & Arica, 2017). Furthermore, it is stated that negative life events experienced at younger ages (such as violence, neglect, abuse, chronic illness) negatively affect the quality of life during the old age period (Yılmaz & Tekin, 2017).…”
Section: Introductionmentioning
confidence: 99%